β Symmetry of Supergravity - Baron, Walter Helmut (2023)
Continuous O(d,d) global symmetries emerge in Kaluza-Klein reductions of D-dimensional string supergravities to D-d dimensions. We show that the nongeometric elements of this group effectively act in the D-dimensional parent theory as a hidden bosonic symmetry that fixes its couplings: the β symmetry. We give the explicit β transformations to first order in α′ and verify the invariance of the action as well as the closure of the transformation rules.